The prognostic significance of central hemodynamics in patients with cardiac amyloidosis. (December 2013) - Russo, Christopher; Green, Philip; Maurer, Mathew
Abstract Background: The diagnosis of cardiac amyloidosis often requires a right heart catheterization with an endomyocardial biopsy. Although the central hemodynamics of the three main types of cardiac amyloidosis (AL, ATTRm, ATTRwt) have previously been described, the prognostic significance of these variables have not been fully explored. Objective: To compare the right heart catheterization variables between the three sub-groups of AL, ATTRm and ATTRwt, and describe if any of these variables are of prognostic significance. Methods: We conducted a retrospective cohort analysis of patients with biopsy confirmed cardiac amyloidosis between 1997 and 2011. Central hemodynamics as well as baseline clinical and laboratory characteristics were collected at the time of diagnosis. The prognostic significance of the central hemodynamics was evaluated. The internal review board of our institution approved the study. Results: Patients with ATTR and AL cardiac amyloidosis had similar central hemodynamic profiles of high filling pressures and low cardiac output with the exception of ATTR having higher pulmonary artery systolic pressure and pulmonary vascular resistance. Right atrial pressure (RAP), pulmonary artery diastolic pressure, pulmonary capillary wedge pressure and pulmonary artery saturation were individual predictors of death or heart transplantation (p < 0.05). However, when each was added to RAP they did not increase the predictive value compared to RAP alone. Conclusion: The central hemodynamics of ATTR and AL amyloidosis were found to be similar and RAP emerged as the main predictor of transplant-free survival.